2017
DOI: 10.1007/s00429-017-1528-6
|View full text |Cite
|
Sign up to set email alerts
|

Neural networks underlying trait aggression depend on MAOA gene alleles

Abstract: Low expressing alleles of the MAOA gene (MAOA-L) have been associated with an increased risk for developing an aggressive personality. This suggests an MAOA-L-specific neurobiological vulnerability associated with trait aggression. The neural networks underlying this vulnerability are unknown. The present study investigated genotype-specific associations between resting state brain networks and trait aggression (Buss-Perry Aggression Questionnaire) in 82 healthy Caucasian males. Genotype influences on aggressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 46 publications
1
14
0
Order By: Relevance
“…Reduced coupling of the SMG with the amygdala after ATD is also in line with findings from neuroimaging genetics, showing that the role of the SMG in aggression-related networks depends on genes influencing serotonin transmission. Specifically, a coupling of the SMG with limbic areas seems to counteract aggressive impulses (Klasen et al, 2018). Reduced connectivity between SMG and amygdala may thus be a neurobiological substrate of increased aggression after ATD (Bjork et al, 1999; Kötting et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduced coupling of the SMG with the amygdala after ATD is also in line with findings from neuroimaging genetics, showing that the role of the SMG in aggression-related networks depends on genes influencing serotonin transmission. Specifically, a coupling of the SMG with limbic areas seems to counteract aggressive impulses (Klasen et al, 2018). Reduced connectivity between SMG and amygdala may thus be a neurobiological substrate of increased aggression after ATD (Bjork et al, 1999; Kötting et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…An established neurobiological model proposes a reduced amygdala regulation due to a blunted serotonergic system as a neurobiological endophenotype in these risk allele carriers (Buckholtz et al, 2008). Recent findings show that trait aggression networks vary as a function of MAOA genotype (Klasen et al, 2018), but the role of serotonin in this brain-behavior relationship is still a matter of debate.…”
Section: Introductionmentioning
confidence: 99%
“…One of these studies concluded that Monoamine oxidase A-L (MAOA-L) carriers (in comparison with MAOA-H carriers) showed that a higher RSFC between the ventromedial prefrontal cortex (vmPFC) and the right angular gyrus (AG), posterior cingulate cortex (PCC), and dorsomedial prefrontal cortex, was related to higher aggression traits. Nevertheless, when the RSFC between the vmPFC and bilateral supramarginal gyrus was high, the aggressive traits were low [37]. The other study revealed that in participants with antisocial personality traits with the MAOA-L variant, high RSFC between the ventral striatal and angular gyrus was related to high proactive aggression [38].…”
Section: Resultsmentioning
confidence: 99%
“…, 2017 ), in overcoming emotional egocentricity bias in social situations ( Silani et al. , 2013 ; Klasen et al. , 2018 ), and in functionally supporting empathy ( Shamay-Tsoory, 2011 ; Coll et al.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, dysfunctions of the temporal–parietal junction, which encompass the SMG, have been shown to contribute to aggressive behavior ( Harenski et al. , 2014 ; Klasen et al. , 2018 ).…”
Section: Discussionmentioning
confidence: 99%